Cover page (Discussion Papers, 2012)
Since the beginning of the 1990s Bulgaria has been experiencing a deep economic and structural restructuring. The transition to market economy in Bulgaria and in the remaining countries of Central and Eastern Europe follows one and the same pattern. The system’s transformation is concurrent with the structural transformation, defined as a process of turning the socialist planning system into a capitalist, market one. The regional inequalities in Bulgaria and Hungary, two small or medium-sized countries of Europe, are rooted in their belated industrial development and in the delay their urbanisation process suffered compared to Western Europe. Their forty years of planned economy could not significantly reduce either their deficiencies in economic potential, or the reasons underlying their regional inequalities. Despite the numerous similarities in the changes that have taken place in the territorial structures of Bulgaria and Hungary, the differences in the responses the two countries gave to the challenges of regional development efforts demonstrate that the ‘Eastern European Bloc” is at least as heterogeneous as the European Union. This collection of studies has been prepared within the cooperation of the Centre for Regional Studies of the Hungarian Academy of Sciences and the Institute of Geography of the Bulgarian Academy of Sciences. The nine studies explore various elements of the transformation such as the two countries’ changing territorial structure, population distribution, public administration, urban network, and the evolution of the legal regulation of regional development.